Pendidikan Perspektif Gravissimum Educationis (Analisis Sosiologis Pendidikan Dalam Terang Dokumen-dokumen Gereja) - Sesfao, Marianus; Bapaq, Paulus (JURNAL PROPHETA, 2021)
This article aims to describe various social problems based on sociological perspective on education issues in this globalization area. As it was assumed thateducation plays more important role to increase some of the interesting parts of those whoconcentrate on that issue in order to maintain the high quality of the education alone. It isbecause the objectivity of the education is human being. By the help of socialization they are capable to maintain the function of educationboth in the society and themselves. Hence, there is a need of social interaction among thehuman being so the role of education should have been functioned well in the society.The authors focused more on education from the point of view of GravissimumEducationis (GE) enriched by the Bible and other documents.